Usability and Utility of Human Immunodeficiency Virus Pre-exposure Prophylaxis Clinical Decision Support to Increase Knowledge and Pre-exposure Prophylaxis Initiations among Pediatric Providers - Chan, Carrie T.; Carlson, Jennifer; Lee, Tzielan; Vo, Megen; Nasr, Annette; Hart-Cooper, Geoffrey (Applied Clinical Informatics, 2022)
Objectives An effective clinical decision support system (CDSS) may address the current provider training barrier to offering preexposure prophylaxis (PrEP) to youth at risk for human immunodeficiency virus (HIV) infection. This study evaluated change in provider knowledge and the likelihood to initiate PrEP after exposure to a PrEP CDSS. A secondary objective explored perceived provider utility of the CDSS and suggestions for improving CDSS effectiveness.Methods This was a prospective study using survey responses from a convenience sample of pediatric providers who launched the interruptive PrEP CDSS when ordering an HIV test. McNemar's test evaluated change in provider PrEP knowledge and likelihood to initiate PrEP. Qualitative responses on CDSS utility and suggested improvements were analyzed using framework analysis and were connected to quantitative analysis elements using the merge approach.Results Of the 73 invited providers, 43 had available outcome data and were included in the analysis. Prior to using the CDSS, 86% of participants had never been prescribed PrEP. Compared to before CDSS exposure, there were significant increases in the proportion of providers who were knowledgeable about PrEP (p = 0.0001), likely to prescribe PrEP (p < 0.0001) and likely to refer their patient for PrEP (p < 0.0001). Suggestions for improving the CDSS included alternative “triggers” for the CDSS earlier in visit workflows, having a noninterruptive CDSS, additional provider educational materials, access to patient-facing PrEP materials, and additional CDSS support for adolescent confidentiality and navigating financial implications of PrEP.Conclusion Our findings suggest that an interruptive PrEP CDSS attached to HIV test orders can be an effective tool to increase knowledge and likelihood to initiate PrEP among pediatric providers. Continual improvement of the PrEP CDSS based on provider feedback is required to optimize usability, effectiveness, and adoption. A highly usable PrEP CDSS may be a powerful tool to close the gap in youth PrEP access and uptake.
Keywords: clinical decision support; electronic health records; adolescent medicine; alert; order set; healthcare providers; pediatric health